Minorías étnicas en la jurisprudencia del Tribunal Europeo y de la Corte Interamericana de Derechos Humanos (2012)
The jurisprudence of the Inter-American Human Rights System has been particularly interested in the protection of indigenous communities as well as the European Human Rights System has taken interest on protecting Roma communities. Studying the case law of both systems will allow us to analyze their scopes for deciding on cases regarding these communities’ human rights protection and materialization.